CLINICAL CHARACTERISTICS AND OUTCOMES OF AN EXOGENOUS THYROTOXICOSIS EPIDEMIC IN PRISON - Pattarawongpaiboon, Chidchanok; Srisawat, Nattachai; Champunot, Ratapum; Somboonjun, Jukrin (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION An outbreak of exogenous thyrotoxicosis is a very uncommon cause of thyrotoxicosis. Little is known about the clinical characteristics and outcomes in these situations. This study aimed to investigate the characteristics and outcome of exogenous thyrotoxicosis and electrolyte imbalance during an outbreak of exogenous thyrotoxicosis in Phitsanulok prison. METHODOLOGY This study collected prospective data during the outbreak of thyrotoxicosis among prisoners at Phitsanulok prison between 29 December 2019 and 17 January 2020. In the first phase, a total of 2,815 prisoners were screened for thyroid stimulating hormone (TSH), potassium levels, and pulse rate. In the second phase, 490 male prisoners were collected for thyroid function tests, serum electrolytes, and urine electrolytes. Thyroglobulin levels were measured in patients with thyrotoxicosis. A questionnaire was used to obtain signs & symptoms of thyrotoxicosis and other pertinent data. RESULTS The prevalence of subclinical hyperthyroidism was 78.1%. Four prisoners died, while 69 prisoners were admitted to the hospital. The pulse rate was significantly higher in the subclinical hyperthyroidism group. Weight loss, palpitation, muscle weakness, and fatigue were found predominantly in the subclinical hyperthyroidism group. The prevalence of hypokalemia was 38.4%, however, there was no difference between subclinical hyperthyroidism and normal TSH. The mean magnesium levels were significantly lower in the subclinical hyperthyroidism group. Hypokalemic patients showed potassium loss through the kidney and was related to hypomagnesemia. Almost all patients with extremely low TSH levels had low normal thyroglobulin levels. The frozen meat during the outbreak had higher levels of thyroid hormone compared to the control group. CONCLUSION This outbreak of thyrotoxicosis, likely due to exposure to exogenous thyroid hormone in frozen meat, raised awareness of nutritional problems in prison. The development of surveillance systems to prevent health outbreaks such as this is urgently needed.